Peran Struktur Modal dalam Meningkatkan Nilai Perusahaan pada BPR - Wita Retenia Gulo; Enik Rahayu (Mahesa Research Center, 2026)
This article aims to analyse the role of capital structure in the management and enhancement of firm value in Rural Banks (Bank Perkreditan Rakyat/BPR) in Bawen, Semarang Regency. The study focuses on how capital structure is understood, formulated, and implemented by BPR management as a strategic policy to maintain operational stability, ensure compliance with banking regulations, and support long-term business sustainability. To address this issue, capital structure theories, particularly the trade-off theory and signalling theory, are employed to explain managerial considerations in financing decisions. Data were collected through in-depth interviews, observation, and documentation, and were analysed qualitatively using a thematic approach. The findings indicate that capital structure in BPR is implemented conservatively by emphasising core capital adequacy and prudent management of third-party funds, in line with the institution’s risk profile and regulatory requirements. A sound capital structure indirectly enhances firm value by strengthening customer trust, reinforcing institutional reputation, and fostering positive perceptions of bank soundness. This study highlights a theoretical contribution by demonstrating that the application of capital structure theories in BPR is contextual and largely influenced by regulatory factors and local characteristics, thus differing from large-scale corporate practices. The novelty of this research lies in revealing the role of capital structure as a trust-based strategic mechanism in enhancing firm value in locally scaled banking institutions.